Digitalization of Public Services Through the Gorontalo Integrated Community (GOMT) Application in Dungingi District, Gorontalo City - Karim, Rahmawati H; Suprapto, Sri Handayani; Karim, Dian Fitriani; Mohi, Widya Kurniati (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Public services are one of the primary functions of government in meeting public needs. With the changing times, digitalization has become a strategic solution for increasing the efficiency, effectiveness, transparency, and accountability of public services. The Gorontalo City Government developed the Gorontalo Integrated Community (GoMT) application to support digital service transformation. This study aims to determine public understanding of the use of the Gorontalo Integrated Community (GoMT) application in Dungingi District, Gorontalo City. This study used a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The results indicate that the digitalization of public services through the GoMT application has not been running efficiently and optimally. The support indicator shows that government support is available in the form of regulations and policies, but public outreach is still minimal, resulting in many residents being unaware of the application. The capacity indicator shows that the availability of human resources is considered adequate, but technological infrastructure remains challenging, such as unequal distribution of internet networks and supporting devices. Meanwhile, the value indicator shows that although the GoMT application has the potential to provide fast, easy, and transparent services, its benefits have not been fully realized because the public still prefers manual services at the village office.Thus, a sustainable strategy is needed, including improving public digital literacy, strengthening network infrastructure, developing simpler and more user-friendly application systems, and consistent budget support. This research is important because it provides a concrete picture of the challenges and opportunities for digitizing public services at the sub-district level. It is hoped that it will provide input for local governments in developing more targeted policies. With these steps, the digitalization of public services through GoMT can be truly realized optimally and more effectively.